910-P: Novel Mechanism of Action Associated with SGLT2 Inhibition, Peripheral Energy Utilization, and CV Benefits in Subjects with Type 2 Diabetes Mellitus and HFrEF - QIN, YUEJUAN; SANCHEZ, NOAH D.; ACOSTA, FRANCISCA M.; MOODY, ALEXANDER; NEPPALA, SIVARAM; TRIPLITT, CURTIS L.; CLARKE, GEOFFREY D.; CERSOSIMO, EUGENIO; DEFRONZO, RALPH A.; SOLIS-HERRERA, CAROLINA (Diabetes (New York, N.Y.), 2024)
Background: SGLT2i is associated with CV benefits, but the mechanisms are not fully elucidated. We report a novel finding associated with improved CV Health in T2D & HFrEF. Elevated ketones, EF%, & heart remodeling have been reported with SGLT2i. This is likely, in part, due to a switch in cardiac metabolism to ketone oxidation. This switch might be present in peripheral tissues, including skeletal muscle (SkM). Objective: To examine the effects of SGLT2i on SkM energy production, utilization, exercise recovery, lipid content, and cardiopulmonary function. Methods n=10(Age= 61.6±3.5, BMI= 31.4±1.8, A1c=7.6%±0.4, EF 32.7%±2.7) were randomized to empagliflozin 25mg vs. placebo 2:1 for 12 wks. SkM 31P & 1H MRS was performed. Cardiopulmonary exercise testing (CPET) was done to assess functional capacity and determine CV prognosis. Results: After SGLT2i, there was a significant improvement in SkM energy production, utilization at rest, and exercise recovery. The VE/VCO2 slope, significantly improved (p<0.05) (Fig.1) Conclusion: We show for the first time that, in subjects with T2DM & HFrEF, SGLT2i significantly improve SkM bioenergetics and lipid content. This was associated with a significant improvement in CV prognostic markers. These findings may explain novel mechanisms of improvement in peripheral bioenergetics that translate into Global CV Health.